ABOUT THE REASONS FOR THE NUCLEATION OF FATIGUE CRACKS ON THE SURFACE OF CONCRETE BANDAGES - Vakulenko, I. O.; Hryshchenko, M. A.; Perkov, O. M. (Science and Transport Progress, 2007)
Cleavage crack formation is a process nucleation caused by the high local stress produced by inhomogeneous elastic-plastic deformation followed by cycles change of temperature in tyre.